Digitalization as a Strategy for Collecting Zakat, Infaq, Shadaqoh (ZIS) Funds during the COVID-19 Pandemic by Lazismu East Java: Digitalisasi Sebagai Strategi Penghimpunan Dana Zakat, Infaq, Shadaqoh (ZIS) pada Masa Pandemi COVID-19 oleh Lazismu Jawa Timur - Prastyo, Dwi; Rachmawati, Imelda Dian (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to describe and explain the application of digitalization in helping to collect zakat, infaq, shadaqoh (ZIS) funds during the COVID-19 pandemic in Lazismu, East Java. This research approach uses a qualitative approach with primary data sources. Data collection was obtained from the results of interviews, observations and documentation. Technical validity of data with triangulation model. The results of this study are the implementation of digital payment systems and digital media in Lazismu, East Java is good. The role of digitalization as a strategy for collecting zakat funds by Lazismu East Java is to provide convenience, expand the market, provide an increasing impact both nominally and non-material zakat funds income. Meanwhile, during the COVID-19 pandemic, the use of digital payment systems was able to raise large amounts of funds amidst the ongoing social restrictions.